STIMULATING ENGLISH LEARNING IN GLOBAL KPOP COMMUNITY ON TWITTER - Dinar Faiza (Journal of Applied Linguistics (ALTICS), 2020)
This study aims to explore the phenomenon of K-pop on Twitter that can be the platform of English learning. The data gathered included writing documents like K-pop tweets, unstructured interviews and survey results. The researcher focused more on taking data from K-poper who use English as EFL (English as a foreign language). Data collection was taken by interview & poll to K-poper, observations and examination of K-pop tweets, included interactions among K-pop community on Twitter. K-pop Tweets was taken randomly with various topics by taking screenshots. The interview conducted by direct messages to some K-popers who gave consents to do the interview. The survey was executed by using Twitterâ€™s poll feature. Data analysis is carried out with a descriptive qualitative method, focused on finding the nature of the particular event on study. The finding of the study revealed that the interest of K-pop stimulates English learning for K-poper. English helps them to support and connect to their interest. The curiosity of K-pop eagers them to learn and improve English skill. It demands their self-learning in the process of improving English skill. English is a bridge to connect them with their K-pop idols. K-pop is boasting their interest to English than studying English in a classroom with a book.Â Keywords: English learning, learning media,K-pop, social media, Twitter